Clinical Epidemiology of Acute Lymphoblastic Leukemia From the Molecules to the Clinic - Manuel Mejia-Arangure, Juan (IntechOpen, 2013)
This book describes different perspectives of childhood acute lymphoblastic leukemia. The approach includes aspects of molecular epidemiology, particularly molecular features that influence the genesis and prognosis of the disease. Some aspects of the prognosis of lymphoblastic leukemias are very detailed, highlighting the use of molecular biology in the early identification of complications that may occur in diseased patients. The authors of the present book conform a Mexican group who identifies the causes of leukemia, and they summarize their experience in research, results and proposals for future studies. A causal model is included in which the authors hypothesized the origin of acute lymphoblastic leukemias, particularly in children. This hypothesis can be useful to better understand other cancers during childhood. This book will help the reader to identify different molecular aspects involved in leukemia, and its relation to the development and evolution of the disease.